2018
DOI: 10.1021/acs.biochem.8b00511
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the Transport Mechanism of the Human Zinc Transporter SLC39A2

Abstract: The human zinc transporter SLC39A2, also known as ZIP2, was shown to mediate zinc transport that could be inhibited at pH <7.0 and stimulated by HCO, suggesting a Zn/HCO cotransport mechanism [Gaither, L. A., and Eide, D. J. (2000) J. Biol. Chem. 275, 5560-5564]. In contrast, recent experiments in our laboratory indicated that the functional activity of ZIP2 increases at acidic pH [Franz, M. C., et al. (2014) J. Biomol. Screening 19, 909-916]. The study presented here was therefore designed to reexamine the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…A series of titratable residues was also identified on TMH 2 (His-63, Glu-67, Glu-70, and Glu-71; Fig. 1 A ), which we suspected might play a role in substrate recruitment to the binding site, or pH sensitivity of transport previously described by our group (14). Additionally, two acidic residues (Glu-106 and Glu-120) were identified, which extend toward the membrane bilayer (Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…A series of titratable residues was also identified on TMH 2 (His-63, Glu-67, Glu-70, and Glu-71; Fig. 1 A ), which we suspected might play a role in substrate recruitment to the binding site, or pH sensitivity of transport previously described by our group (14). Additionally, two acidic residues (Glu-106 and Glu-120) were identified, which extend toward the membrane bilayer (Fig.…”
Section: Resultssupporting
confidence: 57%
“…In contrast, prior work conducted in our laboratory suggested that ZIP2 activity is stimulated rather than inhibited by the presence of H + (13). In a more recent study, we showed that ZIP2-mediated transport in both microinjected Xenopus laevis oocytes and transiently transfected HEK293 cells is independent of both HCO 3 − - and H + -driving forces, but modulated by extracellular pH and voltage (14). However, structural details of how H + affects transport activity are still missing and remain to be described.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, zinc release in the transport cycle of YiiP is driven by conformational changes that alternatively expose the transport site to either side of the membrane surfaces (7). While mammalian ZIP transporters are thought to be operated by a similar alternating access mechanism (5,(24)(25)(26), our data from the bacterial ZIPB support a model in which water dynamics complement metal coordination chemistry to confer mobility to trapped zinc ions, highlighting the functional importance of solvated water in driving zinc transport through a sequence of high-affinity binding sites. Zinc is a defining feature of eukaryotic proteomes that are encoded by ~10% of genomes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Only Zip2 and Zip4 were significantly affected by the Znt7 knockout. Little is known about the function and expression profile of Zip2 [24]. Therefore, the significance of the differential expression of this gene in female Znt7 -/mice is unknown.…”
Section: Plos Onementioning
confidence: 99%